Aqueous cadmium removal with ferrate: Influencing factors, removal mechanism, and effect of coexisting ions. (5th March 2019) - Wang, Hongbo; Zhang, Ru; Li, Haining; Li, Mei; Wang, Yonglei; Zhao, Qian; Wang, Ning
Abstract : Abstract: The aim of the work was to evaluate the potential of potassium ferrate (K2 FeO4, Fe(VI)) removing Cd(II) from aqueous solution and to primarily investigate the mechanism. Batch experiments were carried out to evaluate the influence of various factors including dosage of K2 FeO4, solution pH, the initial concentration of Cd(II), and coexisting ions. The results showed that increasing dosage of K2 FeO4 benefited the removal of Cd(II) with the efficiency up to 98.97%. The enhanced removal occurring at higher pH could be attributed to less self‐decomposition of K2 FeO4 under alkaline conditions. The maximum specific removal capacity was 80 mg/(g K2 FeO4 ) under certain conditions. Surface properties of the Cd(II)‐containing precipitations were characterized, and the results showed that the weakly crystalline ferrihydrite derived from self‐decomposition of Fe(VI) benefited the adsorption capacity, and Cd(II) was removed via the adsorption of the hydrolysate nanoparticles. Moreover, the coexisting ions were found weakening the removal efficiency of Cd(II) due to the restricted activity of K2 FeO4 and competition for adsorption sites of hydrolysate. The interaction between the hydrolyzed products and the adsorbed Cd(II) was also weaken by compressing the thickness of the electric double layer because of the presence of coexisting ions. Practitioner points: Removing Cd(II) from aqueous solution as high as 98.97%. Removal efficiencies of Fe(VI) relied on chemical dose, pH and contaminant concentration. Co‐exiting ions weaken the removal efficiency, such as Ca 2+ and SO4 2‐ as well as ionic strength. Abstract : Fe(VI) removed Cd(II) from aqueous solution effectively as high as 98.97%. Removal efficiencies of Fe(VI) relied on chemical dose, pH, and contaminant concentration. Coexisting ions weaken the removal efficiency, such as Ca 2+ and SO4 2‐ as well as ionic strength.